2018
DOI: 10.48048/wjst.2020.4315
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Work Life among Public Health Nurses: A Survey Comparison between Thailand and Japan

Abstract: Researchers from Thailand and Japan have initiated a collaborative project to compare the Quality of Work Life (QWL) among public health nurses. Thus, the QWL of registered nurses working in a community in Thailand was identified and compared with the Public Health Nurses (PHNs) in Japan. The purpose of which was to determine the similarities and differences between the two countries regarding their nurses’ quality of work life. The 42-item of Brooks’ survey of Quality of Nursing Work Life (QNWL) was translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…The pretesting instrument, reliability was tested, and the results indicated a satisfactory value. This finding was in line with previous studies 17,38 . When considering the results of construct validity testing, the five eliminated items (items: 3, 10, 11, 16, and 20) were deleted, based on a factor loading of less than 0.5.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The pretesting instrument, reliability was tested, and the results indicated a satisfactory value. This finding was in line with previous studies 17,38 . When considering the results of construct validity testing, the five eliminated items (items: 3, 10, 11, 16, and 20) were deleted, based on a factor loading of less than 0.5.…”
Section: Discussionsupporting
confidence: 94%
“…After performing the cognitive interview technique, the findings showed that 23 items needed to be revised to fit each context. This was similar to the earlier version that ensured accuracy by face validity 17 . The pretesting instrument, reliability was tested, and the results indicated a satisfactory value.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The results align with previous study that focused demanding nature of nursing such as quality of work life in humanitarian and crisis settings [ 16 ]. The comparative study involving Thai and Japanese primary health nurses unraveled a modest level of QWL for both groups [ 17 ]. In Bangladesh, a study found that nurses rated their QWL as moderate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%